The United Nations and Business: Towards New Modes of Global Governance?. (May 2015) - Fortin, Carlos; Jolly, Richard
Abstract In the last decade and a half there have been sustained efforts on the part of the United Nations to bring the business sector into formal arrangements for dialogue and cooperation and to codify United Nations policies vis‐à‐vis business in order to give the relationship a more structured footing. This article reviews some of the most prominent of those efforts. In particular, it evaluates the available evidence about the extent to which they are achieving the aim of mobilising the skills and resources of private business for the furtherance of the goals of the United Nations; and about some of the main concerns raised by the UN–business interface, including the possible instrumentalisation of the relationship to gain public legitimacy or as a vehicle for business to influence United Nations policies and actions. It concludes that further research is needed to address these questions in a systematic manner.